Marketing Entrepreneurs Performance of Food and Non-Food SMIS Based on Marketing Entrepreneurs: Entrepreneurship Marketing, Food, and Non-Food SMIs Performance, Balanced Scorecard - Dwi Gemina (International Journal of Economics Development Research (IJEDR), 2020)
Small and Medium Industries (SMIs) is a sector that is quite important in playing a variety of economic interests in national development, especially for the creation of new businesses and jobs. This study aims to analyze the effect of entrepreneurial marketing on the performance of food and non-food SMIs as well as analyze the driving factors and inhibitors of SME performance through a balanced scorecard approach. A sample of 200 registered food and non-food SMIs recorded. The method used a survey method, descriptive, and verification research from—data collection through interviews and distributing questionnaires to business actors. The instrument test conducted through validity, reliability, and ordinal scales raised to interval scale using the method of successive interval for path analysis. The results of the study note that all indicators are valid and reliable together (simultaneously) entrepreneurial marketing has a significant and positive effect on the performance of food and non-food SMIs balanced scorecard approach. Partially (concepts, strategies, methods and market intelligence) significantly and positively influences the production of food and non-food SMIs in the balanced scorecard approach, so that the factors driving performance of food and non-food SMIs in the balanced scorecard approach are concepts, strategies, methods and market intelligence, market methods and intelligence. market methods and intelligence.